A self-talk package for improving figure skating performance by young competitive figure skaters - Ming, S. (Masters Abstracts International, 1993)
A self-talk package consisting of training and both on- and off-ice practice of key words was used with compulsory figure skills in pre-novice and novice level figure-skaters. Performance gains on targeted skills ranged from 7% to 14%, while normal figures remained unchanged. Coaches recommended the procedure of using key words while only one of the four Ss felt that the self-talk was responsible for performance improvement. Implication: Self-talk contributes to skill performance improvement when content is associated with specific skill aspects that are meaningful to the young athlete. However, athlete impressions of the value of the procedure are not correlated with performance improvements. Children's opinions of this procedure's effectiveness are inaccurate.